(untitled) (Research, Society and Development, 2021)
The purpose of the present study was to review the evidence on the benefits of Taekwondo on flexibility in practicing and non-practicing children and adolescents. A search was performed throughout Google Scholar database, including articles published between 2010 and March 2021 and using as descriptors: ’taekwondo’, ’flexibility’, ’range of motion’, and ‘martial arts’. Original research was included and need to write in Portuguese. Three articles were included, which mostly weave positive information about Taekwondo and flexibility. Additionally, students who practice Taekwondo show improvements in flexibility when compared to non-practitioners. Thus, Taekwondo promotes increased flexibility, since the main techniques used use kicks, hip movement, hands, which contribute to better flexibility.